2006
DOI: 10.1021/jp064159v
|View full text |Cite
|
Sign up to set email alerts
|

How Ionic Are Room-Temperature Ionic Liquids? An Indicator of the Physicochemical Properties

Abstract: Room-temperature ionic liquids (RTILs) are liquids consisting entirely of ions, and their important properties, e.g., negligible vapor pressure, are considered to result from the ionic nature. However, we do not know how ionic the RTILs are. The ionic nature of the RTILs is defined in this study as the molar conductivity ratio (Lambda(imp)/Lambda(NMR)), calculated from the molar conductivity measured by the electrochemical impedance method (Lambda(imp)) and that estimated by use of pulse-field-gradient spin-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

159
1,125
15
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,135 publications
(1,318 citation statements)
references
References 74 publications
159
1,125
15
5
Order By: Relevance
“…38 It has been argued that this interaction leads to significant anion-cation pair formation with concomitant loss of the IL ionic character. 38 Although an important interaction between H(2) and the salt ions was expected, the signal of H(2) does not appear in any of the 1 H NMR spectra. This is believed to be caused by the exchange of this acidic hydrogen with deuterium afforded by the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…38 It has been argued that this interaction leads to significant anion-cation pair formation with concomitant loss of the IL ionic character. 38 Although an important interaction between H(2) and the salt ions was expected, the signal of H(2) does not appear in any of the 1 H NMR spectra. This is believed to be caused by the exchange of this acidic hydrogen with deuterium afforded by the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…22 This situation is even more problematic since different dyes and experimental approaches result in significantly different values of solvatochromic parameters for the same ILs. 13,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] For instance, the reported α value for the wellcharacterized IL 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C 4 C 1 im] [NTf 2 ]) varies from 0.51 to 0.86 (cf. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][47][48][49][50][51] It should be highlighted that the hydrogen-bond acceptor strength of an IL is dominated by its anion while the hydrogen-bond donor ability is essentially controlled by the cation and only slightly depends upon the anion of the IL. 18,19 Thus, and since we were focused on developing an extended series for the hydrogen-bond acidity of ILs, ILs comprising a fixed anion ([NTf 2 ] − ) and a wide range of cations (imidazolium-, pyridinium-, piperidinium-, pyrrolidinium-, ammonium-, sulfonium-, and phosphonium-based) were selected.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ILs are described in the literature as Newtonian fluids. [42][43][44][45] Nevertheless, non-Newtonian behaviors have already been reported for some AILs [46][47][48] 49,50 Non-Newtonian shear thinning phenomena have recently been described in several PILs by Burrell et al 50 In this paper, Burrell et al have also investigated the effect of water on this property, and they showed that by increasing the water concentration the rheological behavior of the (PIL þ water) binary system changes from non-Newtonian shear thinning, to Newtonian, to non-Newtonian shear thickening behaviors. 50 More recently, a publication of Guo and Guo reports also that ionic liquid induced structure transition of nonionic wormlike micelles composed of Tween 80 and Brij 30.…”
Section: ' Introductionmentioning
confidence: 99%